Theoretical and Empirical Review of Asset Pricing Models: A Structural Synthesis - Saban Celik (International Journal of Economics and Financial Issues, 2012)
The purpose of this paper is to give a comprehensive theoretical review devoted to asset pricing models by emphasizing static and dynamic versions in the line with their empirical investigations. A considerable amount of financial economics literature devoted to the concept of asset pricing and their implications. The main task of asset pricing model can be seen as the way to evaluate the present value of the pay offs or cash flows discounted for risk and time lags. The difficulty coming from discounting process is that the relevant factors that affect the pay offs vary through the time whereas the theoretical framework is still useful to incorporate the changing factors into an asset pricing models. This paper fills the gap in literature by giving a comprehensive review of the models and evaluating the historical stream of empirical investigations in the form of structural empirical review.